Socio-Economic Attitudes in the Era of Social Distancing and Lockdowns - Kerim Peren Arin; Juan A. Lacomba; Francisco Lagos; Ana I. Moro-Egido; Marcel Thum (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We examine the impact of the rapid spread of the COVID-19 pandemic and the nationwide movement restrictions on socio-economic attitudes in four European countries (France, Germany, Spain, and the United Kingdom). We conducted large-scale surveys while the pandemic rapidly spread before and after nationwide lockdowns were implemented. We investigate the impact in three different categories of attitudes: i) economic perceptions (economic insecurity and views on globalization); ii) political attitudes (trust in domestic and international institutions, populism and immigration); and iii) social aspects (authoritarianism and loneliness). We find that overall, the pandemic/social-distancing, but not the lockdowns, has increased economic insecurity, loneliness, and acceptance of authoritarianism while decreasing support for globalization. On the bright side, there is a sensible increase in trust in domestic institutions. We also document that the pandemic had heterogeneous and disproportional effects both at the country level and at the demographic group level. In terms of societal groups, our results suggest that the aggregate results are mostly driven by a number of groups, most notably women, families with children, and the labor force.
Keywords: D70; H11; H12; H41; I18; 330; lockdown; Covid-19; Europe; economic insecurity; globalization; trust; populism; authoritarianism; social loneliness